Exploring the Unmet Needs of the Patients in the Outpatient Respiratory Medical Clinic: Patients versus Clinicians Perspectives - Lone Birgitte Skov Jensen (International Journal of Chronic Diseases, 2015)
Aim. Developing a theoretical framework explaining patients’ behaviour and actions related to unmet needs during interactions with health care professionals in hospital-based outpatient respiratory medical clinics. Background. The outpatient respiratory medical clinic plays a prominent role in many patients’ lives regarding treatment and counselling increasing the need for a better understanding of patients’ perspective to the counselling of the health care professionals. Design. The study is exploratory and based on Charmaz’s interpretation of grounded theory. Methods. The study included 65 field observations with a sample of 43 patients, 11 doctors, and 11 nurses, as well as 30 interviews with patients, conducted through theoretical sampling from three outpatient respiratory medical clinics in Denmark. Findings. The patients’ efforts to share their significant stories triggered predominantly an adaptation or resistance behaviour, conceptualized as “fitting in” and “fighting back” behaviour, explaining the patients’ counterreactions to unrecognized needs during the medical encounter. Conclusion. Firstly this study allows for a better understanding of patients’ counterreactions in the time-pressured and, simultaneously, tight structured guidance program in the outpatient clinic. Secondly the study offers practical and ethical implications as to how health care professionals’ attitudes towards patients can increase their ability to support emotional suffering and increase patient participation and responsiveness to guidance in the lifestyle changes.